Health Belief Model as Students' Perspective Framework Regarding Covid-19 Prevention - Ismar Agustin; Azwaldi Azwaldi; Nathalia Ramadhanti; Yunike Yunike; Ira Kusumawaty (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
The Covid-19 epidemic have a significant risk to the public's health. The Covid-19 infection spreads swiftly and affects people of all ages. The implementation of health guidelines among students and how students feel they can complete the Covid-19 procedure cannot be separated. The goals of this study is to ascertain how students view Covid-19 prevention from the viewpoint of the Health Belief Model. This research used a descriptive survey with a sample size of 170 respondents and the sampling method is purposive sampling. Descriptive analysis of the components of HBM perceived severity category is quite good (90.0%), perceived barriers is a quite good category (68.2%), perceived benefits is found to be in a quite good category (77.6%), health motivation is in quite a good category (81.2%) and it can be seen that the perception of vulnerability (55.9%) and perception of cues to act (56.5%) was quite good. Positive perceptions include student perceptions of the Health Belief Model's effectiveness in preventing COVID-19, which are rated as being quite good. Therefore, it is envisaged that linked parties would be able to enhance health promotion initiatives for the Covid-19 prevention procedure, both directly and through media like posters put up around campuses